Coin Exchange Machine - Alajmi, Noura (2019)
The Coin Exchange Machine is designed to provide its users with either paper banknotes or coins in exchange of the amount of money they inputted. This project aims to provide efficiency for people when they need change either it be in the form of coins or smaller paper bills. The machine accepts higher Kuwaiti banknotes which are 20KD, 10KD, 5KD, and 1KD as an input. The machine provides in return either smaller banknotes (½ KD, and ¼ KD) or coins(100 Fils, and 50 Fils ) as an output.